Dataset of the HOX1 gene sequences of the wheat polyploids and their diploid relatives - B. Shcherban, Andrey (Data Brief, 2017)
The TaHOX-1 gene of common wheat Triticum aestivum L. (BAD-genome) encodes transcription factor (HD-Zip I) which is characterized by the presence of a DNA-binding homeodomain (HD) with an adjacent Leucine zipper (LZ) motif. This gene can play a role in adapting plant to a variety of abiotic stresses, such as drought, cold, salinity etc., which strongly affect wheat production. However, it's both functional role in stress resistance and divergence during wheat evolution has not yet been elucidated. This data in brief article is associated with the research paper “Structural and functional divergence of homoeologous copies of the TaHOX-1 gene in polyploid wheats and their diploid ancestors”. The data set represents a recent survey of the primary HOX-1 gene sequences isolated from the first wheat allotetraploids (BA-genome) and their corresponding Triticum and Aegilops diploid relatives. Specifically, we provide detailed information about the HOX-1 nucleotide sequences of the promoter region and both nucleotide and amino acid sequences of the gene. The sequencing data used here is available at DDBJ/EMBL/GenBank under the accession numbers MG000630-MG000698.